(untitled) (Acta Scientiarum. Animal Sciences, 2025)
The objective of this study was to evaluate the intake, performance, and economic viability of crossbred Holstein calves (n = 16) fed diets containg different levels of baru meal (Dipteryx alata . Vog) as a replacement for corn (0, 25, 50, and 72%). Total solid feed, concentrate, and forage intake, nutrient intake, weight gain, ingestive behavior, and economic viability were evaluated. Total solid feed and concentrate intake linearly increased (p<0.05) with the replacement of corn by baru meal, however, weight gain (13.7 Kg) was not affected (p>0.05). Baru meal inclusion linearly increased the intake of crude protein, minerals, ether extract, and non-fibrous carbohydrates. Concentrate feeding time exhibited a quadratic effect, with a maximum of 75.92 min. day-1 at 67% replacement. Economic analysis showed that the 50% replacement diet result in higher feed costs but lower cost per kilogram of gain. The inclusion of baru meal up to 72% of corn replacement increased intake without compromising the performance during preweaning phase. A 50% replacement provided the best economic return.